PASTURE MODE FOR USE OF SUDAN GRASS - Nasiyev B.N.; Yancheva H.G.; Zhanatalapov N.Zh. (Scientific Journal of Pedagogy and Economics, 2020)
The main task of fodder production in West Kazakhstan region is to provide the livestock industry with fodders stable in yield, balanced in nutritional value and low in cost. An important point is that the supply of green feed, especially during the summer depression, should not be interrupted. All these requirements are met by Sudan grass. Having high plasticity to growing conditions and unique drought resistance for fodder crops, it becomes an indispensable component of green conveyor. Sudan grass is used as grazing feed, to produce green mass and hay. A significant share of Sudan grass in feed crops is provided by its high nutritional value for farm animals. The research aim is to study the technology of Sudan grass cultivation to provide livestock with full feed. As a result of the carried out studies, the data on productivity and feed value of Sudan grass in conditions of West Kazakhstan region during cultivation in grazing mode were obtained. For the studies in 2018 and 2019 in total for 4 browsing, Sudan grass provided collection of 87.06-107.44 c/ha green mass for use as feed to cattle.